Crystal structure of (1,10-phenanthroline-κ2N,N′)-bis(3-thiophenecarboxylato-κ2O,O′)copper(II), C22H14N2O4S2Cu - Zhang Zhongyu; Men Xiaoxia; Han Bing; Sun Chunyan (Zeitschrift für Kristallographie - New Crystal Structures)
C22H14N2O4S2Cu, orthorhombic, Pbcn (no. 60), a = 20.171(7) Å, b = 9.684(3) Å, c = 10.372(4) Å, V = 2025.9(12) Å3, Z = 4, Rgt(F) = 0.0334, wRref(F2) = 0.0908, T = 273.15 K.